PERAN TENDIK DALAM PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DI UNIVERSITAS SARJANAWIYATA TAMANSISWA - Yuyun Yulia; Trisharsiwi Trisharsiwi; Zainnur Wijayanto; Nimas Sabrina Sintyasakti; Nadya Septiani Rahman; Anggi Yudha Kusuma; Putri Saraswati; Titim Dwi Handayani (Jurnal Dedikasi Pendidikan, 2023)
The Merdeka Belajar dan Kampus Merdeka (MBKM) policy of kemendikbudristekdikti that encourages students to master science from various perspectives and equips students to face changes in science and technology in future. In MBKM, the role of education personnel is to bridge the distribution of information and services that are needed by the academic community. In its implementation, UST plays an active role in MBKM progamme including: Independent Student Exchange, Teaching Campus, and Independent Internship. In the management of MBM, it has been implemented in synergy with Tamansiswa teachings, one of which is honing, caring, and fostering using integrated technology and always improving the professionalism of educational staff.